2020
DOI: 10.1111/cas.14568
|View full text |Cite
|
Sign up to set email alerts
|

The catalytically defective receptor protein tyrosine kinase EphA10 promotes tumorigenesis in pancreatic cancer cells

Abstract: EphA10 (erythropoietin‐producing hepatocellular carcinoma receptor A10) is a catalytically defective receptor protein tyrosine kinase in the ephrin receptor family. Although EphA10 is involved in the malignancy of some types of cancer, its role as an oncogene has not been extensively studied. Here, we investigated the influence of EphA10 on the tumorigenic potential of pancreatic cancer cells. Analysis of expression profiles from The Cancer Genome Atlas confirmed that EphA10 was elevated and higher in tumor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Total RNA isolation, cDNA synthesis, and RT-PCR analysis were performed as previously described with minor modifications [ 51 , 52 ]. Total RNA was isolated from the mouse skin tissues and fibroblasts using TRIzol (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA isolation, cDNA synthesis, and RT-PCR analysis were performed as previously described with minor modifications [ 51 , 52 ]. Total RNA was isolated from the mouse skin tissues and fibroblasts using TRIzol (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were sacrificed 6 weeks after cell injection. The xenograft tumors were recovered to measure tumor weight, fixed in formalin, and were paraffin embedded for histological and immunohistochemical analyses [60].…”
Section: Xenograft Mouse Modelmentioning
confidence: 99%
“…In addition to its role in promoting TNBC, EphA10 upregulation has been shown to promote tumorigenesis in other types of cancer, such as pancreatic (19) and prostate (20) cancers. Indeed, results from The Cancer Genome Atlas (TCGA) RNA-sequencing database showed that the EphA10 mRNA level was significantly higher in tumor tissues than in normal controls in all breast invasive carcinoma (BRCA) subtypes including basal-like TNBC (Supplementary Fig.…”
Section: Epha10 Is Highly Expressed In Cancer Cells and Immunosuppres...mentioning
confidence: 99%
“…Ephrin receptor A10 (EphA10), a member of the Eph subfamily, is not expressed in normal human adult tissue except in the testis ( 16 , 17 ). In contrast, EphA10 expression is common in malignant cells across histology of various tumors and has been associated with poor prognosis in patients with breast, prostate, and gallbladder cancers ( 17 , 18 , 19 , 20 , 21 ). In human breast cancer specimens, expression of EphA10, as assessed by IHC, has been significantly correlated with lymph node metastasis and higher tumor stage ( 22 ).…”
mentioning
confidence: 99%